Studi perbandingan DNA barcoding untuk Bambu - Awaliah, Seli Rizqi; Polosoro, Aqwin (Innovation Centre for Tropical Sciences, 2024)
The Bambusoideae subfamily, a significant group within the Poaceae family, contains diverse genera with complex taxonomic relationships. This study aimed to elucidate the phylogenetic relationships and genetic diversity within the bamboo, focusing on the utility of DNA barcoding markers, i.e., ITS2, matK, and rbcL, in bamboo species identification. By analyzing sequence data from these markers, phylogenetic trees were constructed using the maximum likelihood method to infer evolutionary relationships among species. The results showed that ITS provides the highest resolution for species-level identification, distinguishing closely related species more effectively than matK and rbcL. While matK demonstrated robust genus-level classification, rbcL was limited by its high conservation, making it more suitable for broader taxonomic groupings. These findings contribute to a better understanding of bamboo taxonomy and highlight the importance of marker selection based on the taxonomic resolution required. The study also emphasizes the complementary use of these markers to provide a comprehensive view of bamboo phylogenetics. Keywords: bamboo taxonomy, DNA barcoding, ITS2, matK, rbcL